The relationship between financial reporting on impairment of assets’ value and accounting - Alaa Mohammed Oubaid, Jenan Abd AL-Abbas Al Dulamy, Khadija Jomaa Muter, (Opción, 2020)
The objective of the research is to identify the nature of the concept of impairment of assets, indicators of impairment of fixed assets, and the presentation and analysis of certain related concepts related to impairment of fixed assets included in IAS 36 via comparative qualitative research methods. As a result, there is a relationship between financial reporting on impairment of fixed losses and the appropriate characteristic (property) of accounting information in the company of research sample. In conclusion, the IAS 36 standard requires "impairment of assets" of the economic units by conducting a test at each reporting date to determine